2021
DOI: 10.3390/su13020742
|View full text |Cite
|
Sign up to set email alerts
|

Development of Methods for the Strategic Management of Web Projects

Abstract: In this article, we have explored methods for the strategic management of web projects. By introducing a long-term web project development strategy into the operation of a web project, mechanisms can be developed to improve the efficiency and effectiveness of the web project. An important factor is to develop a strategy taking into account all possible crisis situations and ways out of these situations. The authors analyzed and simulated the web project structure, working out methods of web project strategy re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 18 publications
0
13
0
Order By: Relevance
“…On the other, reputation "persuasiveness" could be useful for coping with the typical free-riding and social-loafing dynamics of social virtual systems. Therefore, a wise use of identifiability features within virtual environments may help in effectively managing online interaction (e.g., Web Projects) [62] and to contrast some dysfunctional dynamics appearing in public information [63].…”
Section: Discussionmentioning
confidence: 99%
“…On the other, reputation "persuasiveness" could be useful for coping with the typical free-riding and social-loafing dynamics of social virtual systems. Therefore, a wise use of identifiability features within virtual environments may help in effectively managing online interaction (e.g., Web Projects) [62] and to contrast some dysfunctional dynamics appearing in public information [63].…”
Section: Discussionmentioning
confidence: 99%
“…This has resulted in the creation of an online extension of the physical world where friends and rivals can speak directly; street gangs have expanded their traditional means of communication (Goldman et al 2014) to adapt to this new reality. The impact of the shift from the physical to the virtual world, especially within the context of social media, can impact the psychological and social dynamics of communication, often requiring a real-world response (see, e.g., Fedushko et al 2021).…”
Section: Gang Violence On Social Mediamentioning
confidence: 99%
“…There are few studies found in the literature that used Neuro-Fuzzy COCOMO, NN for cost estimation [36,37] and cost estimation for web projects [38,39]. Fig.…”
Section: Mmre ¼mentioning
confidence: 99%